CHARACTERISATION OF BIODIESEL PRODUCED USING DOMESTIC WASTE ASH AS CATALYST IN THE TRANSESTERIFICATION STAGE - Kelechi Uche; Ngwu Nwachukwu; Chinwe Alisi; C Ibegbulem (Diponegoro University, 2016)
Domestic wastes ash of unripe plantain peels, palm fruit husks and kola nut pods were used in place of inorganic potassium and sodium in biodiesel production. Analysis of fuel parameters such as Density, Viscosity, Cloud, Pour and Flash points were carried out on the produced biodiesel using the American Standard for Testing Materials ASTM D6751. Quantitative analysis with Atomic Absorption Spectroscopy was done to determine the presence of metals on the 3 ash samples. The result of fuel parameters of Density (mm2/s), Viscosity (mm2/s), Cloud (˚C), Pour (˚C) and Flash (˚C) points gave 0.890±0.007, 5.046±0, 9.0±0.28, 6.5±0.35, 168±1.41 respectively for unripe plantain sample; 0.890±0.01, 5.196±0.00, 9.0±0.56, 6.0±0.14, 168±8.48 for palm fruit husk; 0.895±0.01, 5.912±0.00, 10.25±0.14, 8.0±0.70, 172±2.82 for kola nut pods and 0.886±0.00, 4.813±0.01, 6±0.28, 3±0.00, 165±2.12 for the control sample. Quantitative analysis of the ash samples for metals showed the presence of these metals in the following order K > Na > Pb, Na > K >Pb, K > Na >Pb respectively. The samples studied were found to be rich sources of alkali which can be utilized as alternative to conventional alkali in industries.